Gender Representation in The English Textbook for Grade Ninth in Indonesia - Wafda 'Aini; Elih Sutisna Yanto; Wahyudin Fitriyana (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
This study aims to examine how different genders are represented in Indonesia's grade eight English textbooks. The primary goal of this research is to ascertain the various gender representations and how language and images are used in the English textbook "Think Globally Act Locally." The study employs Fairclough's (1989) Critical Discourse Analysis (CDA) frameworks, specifically the description, interpretation, and explanation. Analyses are divided into five categories: Authors' genders, character genders, issues centered on men or women pictures and visibility, and linguistic traits. Additionally, the images have been subjected to a critical image analysis using the Critical Image Analysis program. The investigation's findings reveal that gender prejudice or stereotypes persist in the English textbooks used in Indonesian schools, despite the government's efforts to promote equality and fairness in education through the country's educational policy. Lastly, the study offers some pedagogical implications and recommendations for resolving gender inequality in the educational materials used in English classrooms.